Greenland whiteout experiments: summer 1960. Summary report. - Jiusto, James E.; Rogers, R. R. (Buffalo, Cornell Aeronautical Laboratory, 1960)
"Prepared for the United States Army Snow, Ice, and Permafrost Research Establishment, Corps of Engineers, under Contract DA-11-190-ENG-100." Mode of access: Internet.